Job or further training? : Impact of the Swiss Basic Federal Vocational Education and Training (VET) Certificate on the careers of low achieving young people - Kammermann, Marlise [Verfasser] (My University, 2010)
"The two-year basic training course leading to the Basic Federal Certificate was established in Switzerland by the new Vocational Training Act in 2002 with the intention of ensuring upper secondary education and training for disadvantaged young people. The purpose of this paper is to discuss the findings of a longitudinal study of youths who participated in a two-year vocational education and training (VET) programme. The main objective is the evaluation of intentions regarding the two-year training course. A sample of 319 trainees on a two-year training course in the retail sales and hotel sectors were questioned at the end of their training about their educational and family background, their occupational and personal situation as well as their prospects. Their integration into the labour market was recorded 14 months later. These results are compared with the results of a sample of 183 graduates of an Elementary traineeship in the same occupational fields." (Autorenreferat, BIBB-Doku)
Keywords: P 1.1 Jugendliche; P 1.7 Benachteiligte; G 1.3.3 Bildungs- & Erwerbsbiografien; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; S 2.3.2 Programme in der Berufsbildung; I 2.2.1 Westeuropa; Benachteiligter Jugendlicher; Benachteiligtenförderung; Berufsverlauf; Berufsgrundbildung; Zweijähriger Ausbildungsberuf; Absolvent; Berufliche Integration; Beruflicher Verbleib; Schweiz